The Role of Arabic Language Teachers in Developing Mahārat Al-Kalām in Class VII Students of MTs. Ira Tembung - Cicin Sutriani; Fatma Yulia (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to analyze the role of Arabic Language teacher and the language skills of MTs Ira Tembung students. This research method uses a qualitative descriptive method with primary data sources in the form of interviews with MTs Ira Tembung's Arabic teacher. The results of this study indicate that the role of the class VII Arabic teacher at MTs Ira Tembung as an educator is able to become a figure, role model, and identification for students and their environment. When the teacher teaches patiently and diligently, his efforts will be seen by the students. They will make their teacher as a role model in the future. The Teacher As Trainer, the education and learning process requires skill training, both intellectual and ability, so that it requires the teacher to act as a trainer. Therefore, the class VII Arabic teacher at MTs Ira Tembung provides training to train students who are not yet able and involve students in many activities and competitions. The development of students' Arabic language skills in Class VII Students of MTs Ira Tembung uses the method of repeating words or sentences (Taqrîr). This initial method is very suitable for low grade students, namely class VII because they are an early stage class who do not understand what Arabic is, so they only need to hear the teacher pronounce new vocabulary and then be followed by class VII students of MTs Ira Tembung and not only the ability to hear the ability to speak (Mahārat Al-Kalām) is the most important ability in language learning because the ability to speak is a basic skill in learning a foreign language. The ability to speak is part of an active and productive language skill. In seeking to develop Arabic speaking skills by practicing pronouncing and distinguishing certain sounds. To practice pronouncing and distinguishing certain sounds students will learn directly through conversation (hiwār). Practice reciting daily conversations using Arabic during lessons in clas